Addressing the Challenges Faced by EndNote Users in Academic Writing (Teacher Half-Yearly Journal, 2025)
The citation management software, notably EndNote, is widely embraced by MPhil and PhD scholars in Nepalese universities. However, its application does not guarantee flawless citation outputs and can present challenges to accuracy. This phenomenological study delves into the complexities faced by EndNote users, focusing on citation inaccuracy issues within EndNote X9 and the American Psychological Association (APA) 7th output style. As an EndNote practitioner, learner, and tutor, I identified various citation accuracy concerns across various source types. The analysis identified two primary contributors to citation inaccuracies: the inherent nature of EndNote reference types and the APA 7th output style, and incorrect entry of information in the reference fields. To address these concerns, modifications were made to EndNote reference types and the output style, and a comprehensive guideline for the accurate entry of information in the reference fields for diverse source types was developed. This research advocates crucial adjustments to both EndNote reference types and the APA 7th output style, alongside meticulous information entry practices, to enhance citation accuracy. The findings contribute to the ongoing discourse on refining citation precision in academic writing, particularly in the context of the Nepalese universities.